Human Resource Management Practices In Procurement Employees at PT. Unhas Hotel And Convention - Adrianah; Rukama Sari (www.amertainstitute.com, 2024)
This study aims to determine the description or picture of Human Resource Management Practices in Employee Procurement at PT. Unhas Hotel and Convention. Data collection in this study uses the Observation and Interview methods. The type of research used in this study is descriptive with a qualitative approach in the form of non-statistics. Based on the results of the study on